Revisiting Trauma: Choreographing the Loss of the Armenian Journalist Hrant Dink - Ersoz, Ayrin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
As a choreography of intervention into daily life, Mihran Tomasyan's Sen Balik Degilsin Ki (SBDK) allows viewers a moment not only to remember the assassination of the Armenian journalist Hrant Dink, but also to revisit past and current traumas that need to be reworked by Turkish and Armenian societies. I argue that the choreography of SBDK functions as a memorialization of a history of losses, using images and objects as guiding elements to trace the roots of the truth. Through their choreographic revaluation, the objects used in SBDK exceed their inherent functionality and gain new meanings marked by Tomasyan's subjectivity.
Keywords: Choreography; trauma; Hrant Dink; artistic subjectivity; choreographic objects; journalists and danger; assassination; loss; dance; memory; Sen Balik Degilsin Ki (SBDK)